Understanding Education Finance for Socio-economic and Political Emancipation - ADELAKUN, Iyanuoluwa Samuel (International Journal of Educational Management, 2021)
It is no longer news that the future of any country depends on the quality of its education which is a key instrument to civilization and development. Education remains the major tool for individual, national, socio-economic development, and eradication of poverty. For effective and efficient implementation of the aims, goals and objectives of the education at all levels, there should be adequate funding of the system. Unfortunately, one of the major problems facing education in Nigeria is the issue of underfunding. One of the reasons for this is the negative influence of politics on education. This has led to slow pace in the development of the educational system in the last few decades. In view of this, the study is set to examine various challenges of education finance in Nigeria, looks into major and alternative sources of finance in education and recommendations is made on how best education finance could be managed for socio-economic and political freedom (Emancipation) in Nigeria.